The Effect of Using Pictures on the Students’ Writing Ability of Grade X at SMA Swasta Kampus Nommensen Pematangsiantar - Frans Putra Hutabarat; Selviana Napitupulu; Christian Neni Purba (International journal of technology and education research, 2026)
This study aims to investigate the effect of using picture media on students’ writing ability in descriptive text at Grade X of SMA Swasta Kampus Nommensen Pematangsiantar. Writing is one of the most important language skills in English learning; however, many students still face difficulties in generating and organizing ideas in written form. Therefore, the use of appropriate instructional media such as pictures is expected to help students improve their writing performance. This research employed a quantitative approach with a quasi-experimental design, specifically the non-equivalent control group design. The sample consisted of two classes: X-1 as the experimental group and X-2 as the control group, with a total of 50 students selected through purposive sampling. The experimental group was taught using picture media, while the control group was taught using conventional methods. The instruments used in this study were pre-test and post-test writing tasks. The data were analyzed using statistical procedures, including mean score comparison and t-test analysis. The findings showed that the experimental class obtained a higher mean score (80.16) compared to the control class (77.44). The t-test result (2.25) was higher than the t-table value (2.01) at a 5% significance level, indicating that the alternative hypothesis was accepted. It can be concluded that the use of picture media has a significant effect on students’ writing ability in descriptive text. Therefore, picture media can be recommended as an effective teaching strategy to improve students’ writing skills in English learning.